2015
DOI: 10.1039/c4cp05205f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically stabilized aliovalent europium-doped magnesium oxide as a UV sensitized phosphor

Abstract: Doping of size mismatched aliovalent ions is challenging due to the associated elastic and electronic stress making the thermodynamics unfavorable. Despite such features, its utilization may be viable if such systems can be made metastable by suppressing the kinetics of phase segregation. In light of such a possibility, we utilize sol-gel synthesis for preparing a size mismatched trivalent europium doped MgO (Mg(1-x)Eu(x)O:(x/2)V"(Mg)) system, which can be potentially used in optical applications. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
(42 reference statements)
2
18
0
Order By: Relevance
“…Previous studies reported that MgO exhibit a broad absorption peak between 260-330 nm (Rastogi et al, 2015). The TEM results exhibited unsatisfactory dispensability of MgONPs due to agglomeration state, and the selected area electron diffraction (SAED) pattern confirmed crystalline nature and cubic shape of MgONPs.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies reported that MgO exhibit a broad absorption peak between 260-330 nm (Rastogi et al, 2015). The TEM results exhibited unsatisfactory dispensability of MgONPs due to agglomeration state, and the selected area electron diffraction (SAED) pattern confirmed crystalline nature and cubic shape of MgONPs.…”
Section: Discussionmentioning
confidence: 76%
“…For example, the compositions Lu 2 O 3 :Gd, Lu 2 O 3 :Ln (Ln = Eu, Sm, Ho, Er, Tm, or Yb), Lu 2 O 3 :Tb, and Lu 2 O 3 :Ln (Ln = Dy or Nd) exhibit host absorption (HA) due to interband transitions, acceptor-like charge transfer (CTT), donor-like ionization (IT), and f → fd transitions, respectively. The sensitization of Ln 3+ ions in most of the non-oxide hosts (LaSi 3 N 5 , GaN, ZnS, and NaYF 4 ) relies on the excitation mechanism such as charge transfer, self-excitation, or via sensitizer-assisted ET; nevertheless, in oxides such as MgO, ZnO, TiO 2 , and WO 3 , the host has strong ability to absorb UV radiation (due to the presence of inherent oxygen vacancies) and transfer it to doped Ln 3+ ions via an ET mechanism presented in Figure b . The presence of a broad and identical band in the excitation spectra of both WO 3 :Eu 3+ and WO 3 :Tb 3+ (discussed above) provides an important evidence in support of ET, thereby ruling out charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…In-depth understanding of ET from the sensitizer to activator Ln 3+ ions is vital for realizing novel luminescence characteristics. Several aspects such as doping levels, sensitizer–activator separation, and host crystallinity with relative band edge position (vis-à-vis ground and excited states of Ln 3+ ions) affect the ET mechanism. A model proposed for the incorporation of Ln 3+ ions (e.g., Eu 3+ , Tb 3+ , Er 3+ , Nd 3+ , etc.) in semiconductor hosts (e.g., ZnS and TiO 2 ) suggests dependence of sensitization efficiency (or antenna effect) on the relative positions of Ln 3+ ground- and excited-state levels vis-à-vis valence and conduction band edges of the host material. ,, As an instance, TiO 2 :Eu 3+ nanoparticles do not display the antenna effect, while TiO 2 :Ln 3+ (Ln = Nd and Sm) produces strong host-sensitized emission due to favorable positioning of Nd 3+ /Sm 3+ energy states and the band edges of the host TiO 2 …”
Section: Introductionmentioning
confidence: 99%
“…The addition of dopants greatly influences the NNP due to the introduction of the strain. The introduction of lower coordinating (Almonacid et al, 2016; Gangwar, Pandey, Sivakumar, Pala, & Parthasarathy, 2013; Rastogi et al, 2017) or high size‐mismatched dopants (J. Lai et al, 2003; Rastogi, Saha, Sivakumar, Pala, & Kumar, 2015; Rastogi et al, 2017) introduces large strain in the lattice structure. To decrease the strain, the crystal undergoes native ➔ non‐native transformation or stabilizes the NNPs at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…When the valence charge densities of host ions and dopants are comparable, it is envisaged that atoms with smaller ionic radii used as dopant will favor the more close‐packed crystal polymorphs in similar reaction condition. However, a high size mismatch between host and dopant would also result in cluster formation of dopants or surface segregation (Rastogi et al, 2015). Similarly, J. Lai et al (2003) showed that in the case of γ‐Fe 2 O 3 was stabilized by Mn (III) dopant up to 600°C temperature.…”
Section: Introductionmentioning
confidence: 99%